Effect of five postemergence herbicides on red clover shoot and root growth in greenhouse studies - Ceballos, Ricardo; Palma, Graciela; Brevis, Hernán; Ortega, Fernando; Quiroz, Andrés (Phytoprotection, 2004)
AbstractMCPA, 2,4-DB, flumetsulam, bentazon, haloxyfop-methyl, flumetsulam/2,4-DB and bentazon/MCPA were studied in greenhouse experiments in order to evaluate their primary effects on red clover (Trifolium pratense) growth and root injury. The influence of these herbicides on root length, plant height, crown diameter, shoot and root dry weights, shoot phytotoxicity and root injury were studied at two application rates. Variable responses in the growth parameters were observed throughout the experimental period. Herbicides did not affect root length. By the end of experiment, plant height was increased by all herbicides except MCPA and bentazon/MCPA. Crown diameter was increased only with MCPA and 2,4-DB, whereas it was not affected by the other herbicides. Bentazon reduced root dry weight while the other herbicides had no effect. In general, MCPA, bentazon, and bentazon/MCPA reduced shoot dry weight. Although all herbicides caused early foliar damage, the plants recovered by the end of expe-riment comparable to the control plants. Bentazon and bentazon/MCPA produced the greatest shoot damage. Roots were injured from all herbicides, yet they usually recovered over time. However, bentazon/MCPA induced more severe root injury, up to 17% of the plants, causing seedlings died. These results suggest that some herbicides used to protect red clover against weeds may also affect red clover development, increasing its vulnerability to disease.